The Religious Innatism Debate in Early Modern Britain - Mills, R.J.W. author. aut Link
IX, 132 p. 1 illus.
Keywords: “A superb study of ideas about the psychological grounds of religious belief and its atheistic shadow in early modern Britain.” —Angus Gowland, University College London, UK “With this impressively erudite and lucid book, Mills recovers a vitally important tradition in European thought that has hitherto been neglected. By debunking the shibboleth that the doctrine of innate religious ideas was consigned to oblivion by Locke, he places Enlightenment intellectual culture in a whole new light.” —Niall O’Flaherty, King’s College London, UK “Why do humans believe in God? Are religious beliefs natural to humanity and held in all societies? It used to be argued that John Locke’s philosophy radically changed how intellectuals answered these questions. In this learned and lucid book, however, Mills shows that Locke’s contribution has been misunderstood, and guides us through a lively debate – in which Locke was one participant among many.” —Alasdair Raffe, University of Edinburgh, UK This book demonstrates that the common belief that humanity is naturally disposed to religion did not disappear with the emergence of the Enlightenment. Going beyond a narrow focus on John Locke’s empiricism, this vivid analysis reconstructs the vociferous, multivocal debate over the natural origins of religious belief in England and Scotland between c. 1650 and c. 1750. It enriches our understanding through examining hundreds of discussions of the relationship between human nature and religion, from a variety of genres and contexts. It shows that belief in religious innatism was a ubiquitous and enduring claim about human nature across the continuum of Christian thought in early modern Britain, and one deployed for a variety of reasons. While the doctrine of innate religious ideas did fall out of use, the belief that human nature was framed for religion continued in new forms into the eighteenth century. R. J. W. Mills is an independent scholar based in London, UK. He was a Leverhulme Early Career Fellow at Queen Mary University of London and previously held Teaching Fellowships at King’s College London and University College London.